Health of aging families: Comparing compound and noncompound caregivers. Issue 3 (3rd April 2022) - Wang, Fei; Marsack-Topolewski, Christina N.; DiZazzo-Miller, Rosanne; Samuel, Preethy S.
ABSTRACT: Providing care to a family member with disabilities takes a toll on the health of the caregiver and the family. Among aging caregivers, compound caregiving (i.e., caring for two or more family members) has become an increasingly common scenario. However, few research studies have focused on compound caregivers. Extant literature describes individual-level outcomes, with sparse knowledge on family-level outcomes. The family quality of life framework was used in this study to examine differences in the individual and family health of aging compound and noncompound caregivers. Web-based cross-sectional data collected from 112 aging caregivers (age 50 and older) were analyzed using chi-square and independent sample t-tests to examine differences between caregivers. Compound caregivers had poorer perceptions of personal health than noncompound caregivers. In terms of family health, although all caregivers shared similar perceptions on the importance, opportunities, initiative, and stability, compound caregivers had lower attainment and satisfaction than noncompound caregivers. Multivariate regression analyses indicated that compound caregiving was associated with poorer family health. Personal health was positively associated with family health. Study findings have practice implications for identifying caregivers' multiple responsibilities. It is necessary to develop individual and family level programs focused on health promotion and caregiver training.